2019
DOI: 10.1039/c9ob02351h
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective construction of 3-aryl-substituted indolines via annulation of in situ generated p-quinone methides

Abstract: A highly diastereoselective [4 + 1] annulation reaction of in situ generated p-quinone methides for the synthesis of 3-aryl-substituted indolines has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…[63][64][65] In particular, Hu et al reported a stereoselective assembly of indolines 89 via a [4 + 1]-annulation with para-quinone methides 88 (Scheme 34). 65 In this method, the generation of the corresponding A 4 -synthons 88 by the oxidation of diarylmethanes 87 was combined in a one-pot process with a subsequent [4 + 1]-annulation reaction with sulfonium ylides. Some derivatives of salicylic aldehyde may serve as A 4 -synthons in [4 + 1]-annulation with ylides.…”
Section: Non-heterodiene Based a 4 -Synthonsmentioning
confidence: 99%
“…[63][64][65] In particular, Hu et al reported a stereoselective assembly of indolines 89 via a [4 + 1]-annulation with para-quinone methides 88 (Scheme 34). 65 In this method, the generation of the corresponding A 4 -synthons 88 by the oxidation of diarylmethanes 87 was combined in a one-pot process with a subsequent [4 + 1]-annulation reaction with sulfonium ylides. Some derivatives of salicylic aldehyde may serve as A 4 -synthons in [4 + 1]-annulation with ylides.…”
Section: Non-heterodiene Based a 4 -Synthonsmentioning
confidence: 99%
“…In 2019, Wang, Zhao, Hu and co-workers reported an effective method for the synthesis of 2,3-dihydroindoles (174), through a base-mediated [4 + 1]-annulation of in situ generated o-tosylaminophenyl-substituted p-QMs (172) with sulfonium ylides (173) [Scheme 44]. [73] A wide range of 2,3dihydroindoles could be accessed in good yields and excellent diastereoselectivities (dr > 20 : 1). Later, the same group developed a one-pot approach for the synthesis 2,3-disubsti-Scheme 42.…”
Section: Synthesis Of Indole Dihydroindole and Isoindoline Based Heterocyclesmentioning
confidence: 99%
“…The key for this catalytic transformation is the dual nucleophilic attack of sulfur ylides in a reaction that proceeds through an azaortho-quinone methide intermediate. [32][33][34][35][36] While the reaction mechanism is entirely different from that of Pd-catalysis, the outcome is almost the same as Pdcatalysis. This transition-metal free protocol was extended to the synthesis of non-fluorinated indolines using methyl, vinyl-or ethynyl-substituted indolines, while the CF 3 -analog was more suitable for this transformation than the others due to the electronwithdrawing property of the CF 3 group.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of combinations of CF 3 ‐benzoxazinones and sulfur ylides were tolerated under those conditions to yield desired CF 3 ‐indolines in moderate to good yields. The key for this catalytic transformation is the dual nucleophilic attack of sulfur ylides in a reaction that proceeds through an aza‐ ortho ‐quinone methide intermediate [32–36] . While the reaction mechanism is entirely different from that of Pd‐catalysis, the outcome is almost the same as Pd‐catalysis.…”
Section: Introductionmentioning
confidence: 99%